0854 The sensitivity of JC virus DNA detection vs JC virus antibody testing in a natalizumab-treated group of relapsing MS patients. Issue 3 (9th February 2012) - Kinsella, K; Kelly, S B; DeGascun, C F; Carr, M; Duggan, M; Hutchinson, M; Tubridy, N; McGuigan, C
Abstract : Introduction: Natalizumab treatment for relapsing remitting multiple sclerosis (RRMS) is associated with a risk of progressive multifocal leukoencephalopathy (PML) due to reactivation of latent JC virus (JCV). We prospectively screened for JCV DNA in urine & serum before treatment to identify those at higher risk of PML. Recently a two-step ELISA test to detect JCV antibodies (JCVAb) as a marker for prior exposure has been developed. Aim: To compare rates of detection of serum JCVAb with those of JCV DNA in serum & urine by PCR in a natalizumab treated cohort. Methods: Qualitative real-time PCR was prospectively used on urine & serum to identify JCV DNA. JCVAb testing by a two-step ELISA technique was undertaken in the same group and results compared. Results: Of 81 patients treated with natalizumab, 36/81 tested positive for JCVAb. JCV DNA in urine was identified in 10/81 (12%) with no positive serum tests; all ten had positive JCVAbs. 26/36 (72%) in the higher risk category for PML had not been identified by PCR. Conclusion: PCR testing detects JCV DNA in blood or urine but does not identify patients with latent JCV. Establishing JCVAb status allows clinicians to more effectively counsel patients with regard to their risk of PML.